Dielectric relaxation and crystallization of nanophase separated 1-propanol-isoamylbromide mixture - VIJ, JAGDISH (My University, 2007)
The effects of liquid-liquid phase separation on molecular relaxation of an apparently homogeneous mixture of 1-propanol and isoamylbromide has been studied by dielectric spectroscopy over a broad frequency and temperature range, and its crystallization kinetics investigated in real time. The mixture shows two widely separated relaxation processes, as before, with the faster relaxation due to the orientational diffusion of isoamylbromide and the slower due to that of 1-propanol. In the mixture, the scaled contribution to permittivity from orientation polarization, ??, of isoamylbromide is about the same as in the pure state, but that of 1-propanol decreases by a factor of ~3 at 120 K. As the temperature is decreased, this difference remains constant. The relaxation time, ?, of isoamylbromide and its distribution parameter remains the same as for the pure liquid, but that of 1-propanol is longer and increases with decrease in T, becoming ~130 times the pure liquid's value at 119 K. This is in contrast to the finding for an isomeric heptanol, whose ? had decreased. Extrapolation suggests that at T>151 K, ? of 1-propanol in the mixture may become less than that in the pure liquid (the isoamylbromide component crystallizes before this temperature could be reached). This indicates that Tg corresponding to ? of 103 s for 1-propanol in the mixture would be higher than in the pure liquid. Crystallization of the two components in the mixture occurs at different rates and 1-propanol remains partially uncrystallized while isoamylbromide completely crystallizes. ? of any remaining liquid isoamylbromide does not change in the presence of crystallized states while ? of residual liquid 1-propanol in the mixture is reduced. The mixture phase separates in submicron or nanosize aggregates of the alcohol in isoamylbromide, without affecting the latter's relaxation kinetics, while its own ?s decreases and ? increases. Consequences of the finding for various relaxation mechanisms are briefly described.
PUBLISHED
Keywords: Electronic & Electrical Engineering